Neglected and Underutilized Crop Species of Nepal: Smart Foods for Uncertain Future - Joshi, Toyanath; Mainali, Ram Prasad; Bhandari, Sabina; Acharya, Prashiksha; Ghimire, Krishna Hari (Journal of Agriculture and Environment, 2023)
The majority of crop species that are cultivated for food in Nepal are not prioritized in formal research, education and development making them neglected and underutilized. A narrative review and expert interviews were carried out to investigate the significance of neglected and underutilized species in the realms of food and nutrition, climate change, economic activities, and culture. We listed 65 neglected and underutilized species as future smart food based on their potential value in food and nutrition. Neglected and underutilized species can play a crucial role by improving incomes and enhancing the food and nutrition security of smallholder farmers and rural communities. Furthermore, these crops have the capacity to adapt against extreme climatic conditions and be tolerant to biotic and abiotic stresses. There is an urgent need to broaden the food basket of the country by supporting the promotion and commercialization of neglected and marginalized crops through research and development.